THE PROBLEM OF STATIN USE IN PATIENTS WITH CARDIOVASCULAR DISEASES AND CONCOMITANT LIVER DISEASES. WHAT DO PRACTICING PHYSICIANS THINK ABOUT IT? - S. Yu. Martsevich; O. V. Lerman; N. P. Kutishenko; A. Yu. Suvorov (Столичная издательская компания, 2015)
Aim. To study the opinion of doctors about the possibility of statins prescription to patients with cardiovascular diseases and concomitant chronic liver diseases. Material and methods. Сross-sectional questioning of the random sample of physicians was performed. Results. 70 physicians (internists - 61.4%, cardiologists - 20.0%, neurologists - 5.7%, endocrinologists - 4.3%, and others) were interviewed. Work experience in the specialty of doctors was 25 years (14; 32.5). 22.9% of doctors completely exclude the possibility of statins prescription to patients with cardiovascular disease if they have concomitant liver disease. 70% of physicians consider it possible to use statin therapy in patients with liver disease, but only under certain conditions. Only a third of them, mostly internists, are ready to prescribe statins under condition of acceptable initial transaminase changes, and almost half of these doctors consider it possible to use statin therapy in patients with concomitant liver diseases only when serum transaminase levels are normal. Conclusion. The physicians often and sometimes unreasonably find it impossible to use statin in patients with cardiovascular diseases and concomitant chronic liver diseases.